Pengembangan Aplikasi Penjualan Berbasis Web dengan Menggunakan Framework Bootstrap Studi Kasus: Toko Morris - Jun Moris M. Sagala; Yulia Ery Kusumawati (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
With the development of information technology today, along with the free trade era almost every company wants to get a market segment that is widest. This is supported by the development of Internet technology and various software on the internet easier for the user. The application of the Internet in a number of business areas are proven strategies to penetrate the global market and get closer to the local and foreign consumers through the Internet, as if the company opened a transaction is spread across various locations. The development of Internet technology can support the rapid adoption of e-commerce systems in product sales. The purpose of this research is to create an e-commerce website is a means of marketing and selling products through the internet. The method used is the method of software development that includes covers analysis software requirements, design, code generation programs, implementation and testing of the unit to an e-commerce website. The conclusion is obtained that the e-commerce website is built using PHP programming language combined with MySQL databases.